A new genus and species of Micropterous Blissidae (Hemiptera: Heteroptera: Lygaeoidea) from Ecuador - Brailovsky, Harry (Zootaxa, 2015)
The new genus Barrerablissus and the new species B. strigosus are described from Napo Province, Ecuador. A key to the known genera of the Western Hemisphere Blissidae with apterous or micropterous condition is included. Dorsal and ventral view and digital photographs of head, pronotum, scutellum, metathoracic scent gland auricle and male genital capsule are added.